Human-mouse xenografts in stem cell research - Wermann, Kai-Christoph; Frühauf, Stefan; Haas, Rainer; Zeller, W. Jens (Journal of hematotherapy, 1996)
New progenitor cell transplantation strategies that change the composition of the graft, such as CD34+ cell selection, ex vivo expansion, and gene marking, are budding. The efficiency and safety of most techniques are evaluated by in vitro assays using human progenitor cells and murine intraspecies transplantation studies before clinical introduction. However, proliferation potential in culture and engraftment capability can be discrepant. Furthermore, some CD34 epitopes and cytokines are unique to humans, thus rendering clinical inferences from experimental results difficult. Therapeutic studies with malignant human hematopoietic cells also require appropriate models that take into account pharmacokinetics. Human-mouse interspecies progenitor cell grafts may allow us to bridge this gap. For engraftment of human cells, recipients need to be immunodeficient. The highest long-term engraftment rate of up to 96% was obtained following transplantation of peripheral blood progenitor cells into non-obese diabetic/severe combined immunodeficiency mice. Data obtained from several human-mouse xenograft transplantation models are presented and discussed.